Association Between the Use of a Digital Health Platform During Pregnancy and Helping Users Avoid Emergency and In-Person Care: Retrospective Observational Study - Hannah R Jahnke; Lily Rubin-Miller; Natalie Henrich; Christa Moss; Neel Shah; Alex Peahl (JMIR Publications, 2023)
BackgroundAlmost one-third of pregnant people visit the emergency room during pregnancy. Although some emergency care is necessary, gaps in patient education and inaccessibility of preventive services have been identified as key reasons for high-cost, low-value care in pregnancy. Digital platforms present a promising solution for providing resources to supplement routine prenatal care, thereby reducing the use of low-value in-person services. ObjectiveThis study aimed to describe the relationship between the use of Maven and in-person care avoidance (emergency room or office visits) during pregnancy. Maven is a digital prenatal health platform that supplements routine prenatal care. Maven offers educational content (articles, videos, and classes), care coordination (through a care advocate), and provider services (web-based appointments and communication with providers) designed to complement prenatal care. Specifically, the aims of this study were to examine whether the use of Maven is associated with in-person care avoidance overall and whether improvements in pregnancy-related knowledge facilitate in-person care avoidance. To assess aim 2, we tested if the use of Maven is associated with improvements in self-reported understanding of warning signs and medically accurate information and if self-reported understanding of medically accurate information and warning signs is associated with in-person care avoidance in a population of Maven users. MethodsIn this retrospective study, we used adjusted logistic regression to examine the relationship between digital platform use, avoidance of in-person care, and the platform's influence on pregnancy-related knowledge (learning medically accurate information and recognizing warning signs). Demographics, medical history, and in-person care avoidance were self-reported. ResultsOf the 5263 users, 280 (5.32%) reported that Maven helped them avoid in-person care during pregnancy. More users who reported avoiding in-person care also reported that the digital platform helped them understand warning signs (231/280, 82.5%) and learned medically accurate information (185/280, 66.1%). In the adjusted models, all modes of digital service use (assessed as quartiles) were associated with avoiding in-person care in a dose-response manner (eg, web-based provider appointments: Q2 adjusted odds ratio [aOR] 1.57, 95% CI 1.00-2.41; Q3 aOR 2.53, 95% CI 1.72-3.72; Q4 aOR 5.26, 95% CI 3.76-7.42). Users were more likely to avoid in-person care if they reported that Maven helped them recognize warning signs (aOR 3.55, 95% CI 2.60-4.94) or learn medically accurate information (aOR 2.05, 95% CI 1.59-2.67). ConclusionsThese results suggest that digital platforms can be effective in helping patients to avoid in-person care. The educational pathway suggests that digital platforms can be particularly effective in helping patients recognize warning signs and learn medically accurate information, which may help them avoid in-person care by recognizing when in-person care is medically appropriate. Future work is needed to assess other pathways through which digital resources can support pregnant people and improve perinatal care use.